Weed Management in Rice - Dennis C. Odero; Curtis Rainbolt (EDIS)
Successful weed control is essential for economical rice production in the Everglades Agricultural Area (EAA). Refer to this revised 5-page fact sheet for current management recommendations. Written by D.C. Odero and C. Rainbolt and published by the UF Department of Agronomy, March 2011.